The tourist experience: an experience of the frameworks of the tourist experience? - Hécate Vergopoulos (Via@)
This contribution aims to produce a critical literature review of the recent collaborative works dealing with the notion of tourist experience (Sharpley and Stone, 2012; Filep and Pearce, 2013; Prebensen, Chen and Uysal, 2014; Decroly, 2015). Organized around four questions (what is not/does not produce experience in tourism?, what is the use of the tourist experience?, what is an unsuccessful tourist experience? and can forms of inauthentic experiences exist?), it particularly tries to highlight what these studies, stemming from different disciplines and traditions of research (management sciences, psychology, geography, anthropology, education sciences, etc.) have in common. It also intends to show that through the plurality of approaches emerge zones of friction and tension in the definition of this central notion of tourism.It thus shows that there are today three main approaches to this notion: in a first sense, the tourist experience can be understood as “everything that happens in a tourist situation”. In a second sense, the tourist experience can be conceived as a learning process of the different world and otherness. Finally, within the framework of the third approach, which is highly influenced by management sciences, it becomes a program for consumption for tourist action. This last meaning in particular highlights the fact that the tourist experience thus defined is perhaps less the experience of otherness than the experience of the consumption of another, or, to say it differently, the fact that the tourist experience is maybe ultimately only an experience of the frameworks of tourist consumption.